THE INFLUENCE OF USING SEMANTIC MAPPING TO TEACH WRITING NARRATIVE TEXT - Nadia Tsyifa Husnulhanifah; Elisa Nurul Laili (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2023)
This study aims to obtain empirical evidence about the use of semantic mapping in learning to write narrative texts in class X MAS Integrated Al-MUnawaroh. The method used is a quantitative method with a quasi-experimental design. The sample in this study were students of class X-A as the experimental class and X-B as the control class. The instrument in this study is a test. Tests were carried out before and after students received treatment. The average pretest score for the experimental class was 57.69, while the control class was 49.74. The student's writing ability in the experimental class and control class during the pre-test was still constrained by vocabulary and differences in text. The average value of the posttest in the experimental class was 72.60 and that of the control class was 63.77. The writing ability of the experimental class students improved more than the control class. The results showed that the average value of the class that used semantic mapping was higher than the class that was not given treatment. Therefore, it can be concluded that there is a significant increase in the effect of using semantic mapping on learning to write narrative texts for class X MAS Al-Munawaroh Integrated Academic Year 2022/2023.